The Research Data Management Organiser (RDMO) – a Strong Community Behind an Established Software for DMPs and Much More - Anders, Ivonne; Enke, Harry; Hausen, Daniela Adele; Henzen, Christin; Jagusch, Gerald; Lanza, Giacomo; Michaelis, Olaf; Peters-Von Gehlen, Karsten; Rathmann, Torsten; Rohrwild, Jürgen; Schönau, Sabine; Wedlich-Zachodin, Kerstin Vanessa; et al. (Data Science Journal, 2024)
This practice paper provides an overview of the Research Data Management Organiser (RDMO) software for data management planning and the RDMO community. It covers the background and history of RDMO as a funded project, its current status as a consortium and an open source software and provides insights into the organisation of the vibrant RDMO community. Furthermore, we introduce RDMO from a software developer’s perspective and outline, in detail, the current work in the different sub-working groups committed to developing DMP templates and related guidance materials.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Community building; Data management planning; DMP templates; DMP tool; Open source software